2004
DOI: 10.4269/ajtmh.2004.71.646
|View full text |Cite
|
Sign up to set email alerts
|

Household Survey of Dengue Infection in Central Brazil: Spatial Point Pattern Analysis and Risk Factors Assessment

Abstract: Urban dengue fever is now considered a major public health threat in most American countries. A household survey was conducted in the city of Goiania in central Brazil in 2001 to assess prevalence of dengue infection and individual and area-based risk factors. Spatial point pattern analysis was performed using the dual Kernel method. A total of 1,610 households were surveyed; 1,585 individuals more than five years old had blood and data collected. Sera were tested for IgM/IgG antibodies by an enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
33

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 31 publications
(23 reference statements)
6
97
0
33
Order By: Relevance
“…This was consistent with the study reported from Brazil [13] [14]. In our study, the finding was perhaps expected as Garden is a modern urban area with high rise buildings and inhabited by affluent communities.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This was consistent with the study reported from Brazil [13] [14]. In our study, the finding was perhaps expected as Garden is a modern urban area with high rise buildings and inhabited by affluent communities.…”
Section: Discussionsupporting
confidence: 83%
“…Our study also showed greater preponderance of dengue IgG antibodies in males compared to females. Where reports suggest no significant differences associated with sex that might be different from Pakistan's perspective owing to the fact that majority of the females remain indoors while males spend their maximum time outside [11]- [13]. As mentioned previously, the dengue vectors are highly adaptable to any environment, hence it is probable for male children of such ages to become exposed to its habitat more often and contracting the virus.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, serological surveys to determine the seroprevalence or seroincidence of dengue antibodies In order to estimate the real magni- 23 , Salvador (67%) 20 , Niterói (66%) 34 , Macapá (48.4%) 23 , Rio de Janeiro (44.5%) 30 , Fortaleza (44%) 21 , and São Luís (41.4%) 22 . Lower rates were found in Goiâ-nia (29.5%) 35 , Belo Horizonte (23.3%) 26 , and Ribeirão Preto (5.4%) 36 . The variations result from the diversity in the distribution of determinant factors in each geographic space in this country of continental dimensions, particularly in the climatic diversity and population density, in addition to the time elapsed between the initial viral circulation and the serological surveys, the circulating serotypes, and other factors.…”
Section: Revisiting Dengue Epidemiology In Brazilmentioning
confidence: 94%
“…Brazil has the most cases of dengue fever in the Western Hemisphere; ≈70% of all cases are reported, and of this total, 17% are concentrated in the Amazon region of Brazil (23). When the risk factors for a dengue epidemic in Goiânia in the Central-West region of Brazil were analyzed, Siqueira et al (24) noted a higher dengue prevalence among those with a lower educational level. This fi nding differs from our results and again highlights the specifi cities of disease in this region.…”
Section: Discussionmentioning
confidence: 99%